2022
DOI: 10.1167/jov.22.2.12
|View full text |Cite
|
Sign up to set email alerts
|

Matching convolved images to optically blurred images on the retina

Abstract: Convolved images are often used to simulate the effect of ocular aberrations on image quality, where the retinal image is simulated by convolving the stimulus with the point spread function derived from the subject's aberrations. However, some studies have shown that convolved images are perceived far more degraded than the same image blurred with optical defocus. We hypothesized that the positive interactions between the monochromatic and chromatic aberrations in the eye are lost in the convolution process. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 63 publications
(89 reference statements)
0
1
0
Order By: Relevance
“…Although from optical principles subjective depth-of-focus [ 11 ] or image quality score [ 101 103 ] using convolved images through corrected optics or real aberrations should match [ 103 ], Vincent et al [ 103 ] observed a difference of about 20 and 35% between simulated and real optical blur, respectively, in the presence of spherical and astigmatism blur. Aissati et al [ 105 ] demonstrated that, when keeping all other conditions similar in both experiments, the discrepancies found using polychromatic targets further reduced when the experiment was conducted in monochromatic light, as monochromatic and chromatic aberrations interact differently in both conditions.…”
Section: Lumin Ens Paris-saclay - Crx1 Adaptive Optics Visual Simulatormentioning
confidence: 99%
“…Although from optical principles subjective depth-of-focus [ 11 ] or image quality score [ 101 103 ] using convolved images through corrected optics or real aberrations should match [ 103 ], Vincent et al [ 103 ] observed a difference of about 20 and 35% between simulated and real optical blur, respectively, in the presence of spherical and astigmatism blur. Aissati et al [ 105 ] demonstrated that, when keeping all other conditions similar in both experiments, the discrepancies found using polychromatic targets further reduced when the experiment was conducted in monochromatic light, as monochromatic and chromatic aberrations interact differently in both conditions.…”
Section: Lumin Ens Paris-saclay - Crx1 Adaptive Optics Visual Simulatormentioning
confidence: 99%